Problematic issues of accounting and analysis of financial results - M. I. Morozova; N. A. Lazareva; N. V. Moskalenko; T. N. Sharonina (Путеводитель предпринимателя, 2021)
Analysis of the financial performance of companies and organizations allows you to evaluate the final result obtained in the process of carrying out activities. An open market environment has not yet been created in Russia, so the analysis of the financial results of companies and organizations will always be used to assess the profitability of companies. The main source of analysis is financial results, the ratio of income and expenses. The statement of financial results is especially interesting because it can show various income, expenses and financial results of a company.